2020
DOI: 10.4236/ojbm.2020.84101
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of COSO Preventative Control Operations on Revenue Mobilization in Ugandan Schools

Abstract: This article provides informative insights into the failure of many Stakeholders to attain the desired Ugandan private secondary schools, to realise their desired revenue and how that failure has caused critical investment concerns due to negative impacts on expected returns on investment. Therefore, the study drew upon that to explore whether preventive control practices within the COSO control activities contribute to this failure. The study used an interpretivism approach and was guided by conceptual COSO c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…In other studies, Nantunda et al (2020) demonstrated how reviewing and validating internal controls and adhering to authorization processes had a favorable impact on financial performance. The research mentioned above demonstrates that a connection between organizational effectiveness and authorization exists, though the empirical findings were based on businesses in various industries.…”
Section: Effect Of Control Activities On the Revenue Generationmentioning
confidence: 94%
“…In other studies, Nantunda et al (2020) demonstrated how reviewing and validating internal controls and adhering to authorization processes had a favorable impact on financial performance. The research mentioned above demonstrates that a connection between organizational effectiveness and authorization exists, though the empirical findings were based on businesses in various industries.…”
Section: Effect Of Control Activities On the Revenue Generationmentioning
confidence: 94%